Biting Midges of the Forcipomyia (Forcipomyia) argenteola group in southern South America, with description of a new species and a key to the Neotropical species (Diptera: Ceratopogonidae) - Marino, Pablo Ignacio (2008)
A new species of the Forcipomyia (Forcipomyia) argenteola group, F. (F.) donatoi, is described and illustrated from males and females collected in several localities of northern Argentina and in Paraguay. The new species is compared with the similar congeners F. (F.) marini and F. (F.) uramaensis, both from Venezuela. The following three species: Forcipomyia (F.) argenteola, F. (F.) calatheae and F. (F.) quatei are recorded for the first time from Argentina, and a key is presented for the identification of the seven Neotropical species of the group.